“Positive” and “Negative” Rights: Shortcomings of the Church’s Social Teaching - Martino, Beniamino Di (International Journal of Humanities and Social Science Research, 2016)
After taking a somewhat biased and rather paternalistic approach towards human rights, the official teaching of the Catholic Church hurriedly converted to proclaiming such rights with great conviction, although in a much broader but less precise way. Nevertheless, there was a risk of adding error to error: the past “error” which did not consider the metaphysical reach of individuals’ natural rights (especially in terms of the duty to resist growing political power) and the present “error” which is broadly based on a way of thinking that tries to match needs with rights (very broad legitimization of the authority of the State but seriously compromising individual liberties). Unfortunately, the Social Doctrine of the Church, according to Popes, demonstrates the lack of the realism and the doctrine of natural law that the libertarian tradition has expressed to guarantee individual natural rights and freedoms.